2009
DOI: 10.1103/physrevlett.102.025502
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Relaxation and Intermixing in Ge Islands Grown on Pit-Patterned Si(001) Substrates

Abstract: We compare elastic relaxation and Si-Ge distribution in epitaxial islands grown on both pit-patterned and flat Si(001) substrates. Anomalous x-ray diffraction yields that nucleation in the pits provides a higher relaxation. Using an innovative, model-free fitting procedure based on self-consistent solutions of the elastic problem, we provide compositional and elastic-energy maps. Islands grown on flat substrates exhibit stronger composition gradients and do not show a monotonic decrease of elastic energy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 27 publications
7
70
2
Order By: Relevance
“…increases rather monotonically along the growth direction, consistent with XRD results for domes grown on patterned substrates [24]. However, the first barn B 1 shows some deviation from this commonly observed trend: we see in fact a relatively Ge-poor region sandwiched between a Ge-rich top shell and the bottom core [ Fig.…”
Section: Sb Andsupporting
confidence: 86%
“…increases rather monotonically along the growth direction, consistent with XRD results for domes grown on patterned substrates [24]. However, the first barn B 1 shows some deviation from this commonly observed trend: we see in fact a relatively Ge-poor region sandwiched between a Ge-rich top shell and the bottom core [ Fig.…”
Section: Sb Andsupporting
confidence: 86%
“…The latter four features are of particular importance if NHE is benchmarked against other deposition techniques used to achieve Ge nano-islands such as the Stranski-Krastanov growth of Ge on planar Si substrates, which leads to randomly distributed, highly intermixed, size inhomogeneous self-assembled islands [12][13] . Pit-patterned Si substrates have been utilized to improve ordering and size uniformity [14][15][16][17][18] but with this approach Si-Ge intermixing is not prevented owing to the rather high process temperature required to achieve selectivity and high crystal quality 15,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use the SiGe/Si as a model system to show the predictive capability of the method. The reason that we use this model system is because the measurements of the composition profiles, as well as the shape of the nanocrystals, have been recently performed [17][18][19] . Therefore, let us begin by setting A = Si, B = Ge.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that reciprocal space mapping method from Xray diffraction 17,19 and composition-selective chemical etching 18 are both techniques capable of reconstructing composition profiles in cross-section. The measurements [17][18][19] showed that Ge atoms accumulate at the top of the island and silicon atoms prefer to stay at the bottom. The composition at the central part of the island appears to be relatively uniform with a composition close to the average between the top and bottom of the islands.…”
Section: A Cross-sectional Composition Profilesmentioning
confidence: 99%